Solar Cells: A–D–A‐type S, N‐Heteropentacenes: Next‐Generation Molecular Donor Materials for Efficient Vacuum‐Processed Organic Solar Cells (Adv. Mater. 42/2014). (November 2014) - Mishra, Amaresh; Popovic, Dusko; Vogt, Astrid; Kast, Hannelore; Leitner, Tanja; Walzer, Karsten; Pfeiffer, Martin; Mena‐Osteritz, Elena; Bäuerle, Peter
<x xml:space="preserve">Abstract</x> A novel class of multifused heteroacenes, developed and introduced by P. Bäuerle and co‐workers on page 7217, combines the favorable structural and electronic elements of oligothiophenes and acenes. Their application in organic photovoltaics leads to encouraging power conversion efficiencies of 6.5%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>